Antecedents of Psychological Well-Being in Adolescents: a Systematic Literature Review - Siti Muzaro’atut Dawamah; Nida Hasanati (Journal of Social Research, 2026)
Adolescent psychological well-being is a critical issue influenced by the complex interaction of various factors. This systematic review aims to identify and map key antecedents affecting adolescent psychological well-being based on current literature. The PRISMA method was applied through a search of electronic databases including Google Scholar, APA PsycNET, Springer, and Elsevier. Of the identified articles, 11 journals met the inclusion criteria after a rigorous selection process. The analysis revealed various antecedents that can be classified into protective and risk factors. Social support emerged as the most dominant antecedent, followed by self-esteem and resilience, which play a significant role in improving adolescent psychological well-being. Meanwhile, key risk factors identified included stress, bullying experiences, and poor social relationships, which were consistently associated with decreased psychological well-being. These findings underscore the importance of a multidimensional approach to intervention efforts, where strengthening protective factors needs to be carried out simultaneously with mitigating risk factors. Effective interventions should integrate the adolescent's family, school, and social contexts to support optimal psychological well-being.